Effect of maternal exercise during pregnancy on maternal body components and fetal growth in young and adult rats. - de-Mello, M. A. [UNESP] (My University, 1990)
In order to investigate the effects of exercise training on maternal adiposity and fetal development, young Wistar rats (45-50 days old) were divided into four groups: control non-pregnant, control pregnant, exercise-trained non-pregnant and exercise-trained pregnant. Four equivalent groups of adult rats (90-100 days old) were also used. Trained rats swam 1 h/day, 5 day/week throughout pregnancy or for a 22-day period (non-pregnant rats). Physical activity during the entire gestational period reduced weight gain during pregnancy. Both control and trained pregnant rats showed an increase in food intake during the 2nd week of pregnancy and increased food efficiency. Exercise training reduced perirenal fat weight in young and adult pregnant rats. Muscle protein content, litter size and birth weight of pups were similar for control and trained rats. These results indicate that the energy expenditure required during exercise training by both young and adult pregnant rats reduces depot fat and does not seem to alter normal gestation. Counterregulatory mechanisms during pregnancy and exercise training result in increased food efficiency which probably preserves both maternal and pup metabolism.